2016
DOI: 10.2174/1381612822666151211094901
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Aspects of the Endocannabinoid System (ECS) for Cancer and their Development: From Nature to Laboratory

Abstract: The endocannabinoid system (ECS) is a group of neuromodulatory lipids and their receptors, which are widely distributed in mammalian tissues. ECS regulates various cardiovascular, nervous, and immune system functions inside cells. In recent years, there has been a growing body of evidence for the use of synthetic and natural cannabinoids as potential anticancer agents. For instance, the CB1 and CB2 receptors are assumed to play an important role inside the endocannabinoid system. These receptors are abundantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 116 publications
0
46
0
Order By: Relevance
“…It plays an important role in the organism's physiology. Dysregulation of the endocannabinoid system, owing to variation in the expression and function of cannabinoid receptors or enzymes or the concentration of endocannabinoids, has been associated with several diseases, such as neurodegenerative disorders, multiple sclerosis, inflammation, epilepsy, schizophrenia, glaucoma, cardiovascular diseases, obesity and cancer [3,4]. In recent years, further components have expanded this original definition of the endocannabinoid system.…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in the organism's physiology. Dysregulation of the endocannabinoid system, owing to variation in the expression and function of cannabinoid receptors or enzymes or the concentration of endocannabinoids, has been associated with several diseases, such as neurodegenerative disorders, multiple sclerosis, inflammation, epilepsy, schizophrenia, glaucoma, cardiovascular diseases, obesity and cancer [3,4]. In recent years, further components have expanded this original definition of the endocannabinoid system.…”
Section: Introductionmentioning
confidence: 99%
“…In fact our study supports the hypothesis that metastatic RCC could potentially become the disease of interest for metabolic oncology research ( 27 ). Terpenoids currently used in humans constitute 6 major drug classes: steroids, tocopherols, taxanes, artemisinins, ingenanes and cannabinoids, all of which are of potential interest in oncology ( 28 ). As terpenoids are useful in the prevention and therapy of several diseases, including cancer, and also have anti-spasmodic, antimicrobial, anti-parasitic, anti-fungal, anti-viral, anti-allergenic, anti-hyperglycemic, anti-inflammatory, and immunomodulatory properties, the deregulation of their transport into the cells may significantly impact RCC treatment, but may also represent a novel therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic action of both mentioned compounds has been studied principally in glioblastoma. [59,60] On the other hand, it has been demonstrated that endocannabinoid signalling is enhanced in some human cells malignancies compared with corresponding healthy tissues [61,62] , and in neoplastic cells with high invasiveness. [63] ECS has an emerging modulating activity on nuclear factors and proteins that regulate cell differentiation, survival and proliferation.…”
Section: Cannabinoids and Endocannabinoids Pharmacology In Cancermentioning
confidence: 99%